Identification of the novel HLA‐DQB1*02:85 and HLA‐DRB1*01:01:30 alleles in Russian individuals. (3rd May 2017) - Kuzmich, E.; Tyapushkina, S.; Alyanskiy, A.; Afanasyev, B.
Abstract : Two novel HLA class II alleles, HLA‐DQB1*02:85 and HLA‐DRB1*01:01:30, were detected in Russian individuals.